2015
DOI: 10.1155/2015/153805
|View full text |Cite
|
Sign up to set email alerts
|

Serum Endocan as a Survival Predictor for Patients with Liver Cirrhosis

Abstract: BACKGROUND: The relationship between endocan expression and outcome in patients with chronic liver disease is not fully understood.OBJECTIVE: To examine whether serum endocan level is predictive of outcome in patients with liver cirrhosis.METHODS: A total of 68 patients with liver cirrhosis were enrolled. Outcome predictors were analyzed using the Cox proportional hazards model. The overall survival rates were calculated using the Kaplan-Meier method, and differences were evaluated using the log-rank test.RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Interestingly, Sparcl1 is also induced in HSC in nonalcoholic steatohepatitis (NASH), but not toxic liver fibrosis [30]. Esm1 and Igfbp5 were also significantly regulated angiocrine factors in LSEC of Gata4 LSEC-KO mice and they are known biomarkers for liver fibrosis involved in HSC activation [31,32].…”
Section: Analysis Of Single Cell Rna-seq Data Reveals That the Endothmentioning
confidence: 99%
“…Interestingly, Sparcl1 is also induced in HSC in nonalcoholic steatohepatitis (NASH), but not toxic liver fibrosis [30]. Esm1 and Igfbp5 were also significantly regulated angiocrine factors in LSEC of Gata4 LSEC-KO mice and they are known biomarkers for liver fibrosis involved in HSC activation [31,32].…”
Section: Analysis Of Single Cell Rna-seq Data Reveals That the Endothmentioning
confidence: 99%
“…Since ED seems to intervene in the pathogenesis and natural history of NAFLD, it might be useful to identify an ED biomarker in this setting. Recently, a novel serum biomarker called Endocan (ESM-1) has been found to predict the overall survival in patients with liver cirrhosis [22]. ESM-1 is a 50 kDa circulating proteoglycan specifically produced by non sinusoidal endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In their study Toshikuni and his group [11] concluded that endocan might be an independent survival predictor for patients with cirrhosis. Our results also favour a role for endocan as a prognostic marker for worse outcome in cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have convincingly shown that endocan is involved in the mechanisms of acute inflammation and neovascularization in various pathological conditions such as sepsis [3,4] and tumor progression [5] and recent data shows a role for endocan as an indicator of cardiovascular disease [6]. While its value as a diagnostic or prognostic marker for hepatocellular carcinoma is under investigation [7][8][9], there have been few papers on endocan in the setting of liver cirrhosis [10,11].…”
Section: Introductionmentioning
confidence: 99%